2003
DOI: 10.1177/014556130308201013
|View full text |Cite
|
Sign up to set email alerts
|

Middle Turbinate Resection: Impact on Outcomes in Endoscopic Sinus Surgery

Abstract: There is considerable controversy conce rning the advisability and efficacy ofmiddle turbinat e resection in endoscopic sinus surgery. Some have reported that it causes an increase in the incidence offrontal sinusitis, while others have fo und 110 such association. Surprisingly, in a 35year review of turbinate surgery literature, Clement and White did notfind a single prospective study ofturbinat e surgery. In this article, we briefly report our pro spective study of middle turbina te resection during endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 5 publications
1
21
0
4
Order By: Relevance
“…A great number of reviews have been published attempting to address the issues surrounding middle turbinate resection. By and large, studies have failed to show significant deleterious effects related to middle turbinate resection, such as atrophic rhinitis, nasal obstruction, or olfactory loss 4, 5, 16, 17. Several studies have actually shown statistically significant but relatively modest increases in maxillary ostial patency rates after middle turbinate resection 18.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of reviews have been published attempting to address the issues surrounding middle turbinate resection. By and large, studies have failed to show significant deleterious effects related to middle turbinate resection, such as atrophic rhinitis, nasal obstruction, or olfactory loss 4, 5, 16, 17. Several studies have actually shown statistically significant but relatively modest increases in maxillary ostial patency rates after middle turbinate resection 18.…”
Section: Discussionmentioning
confidence: 99%
“…There are those who favor anterior middle turbinate preservation [23], and others who practice total or partial middle turbinate resection [24]. However, none of the surgeons have provided any scientific rationale for their approaches [25]. In a study, a gel foam patch was packed to keep the neo-ostium open throughout the healing period after endonasal DCR [26], and similarly, in all group 2 patients, we packed antibiotic-soaked cotton pledget in the sac under endonasal endoscopic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined by Wolf et al (Wolf and Biedlingmaier, 2001), arguments for and against MT resection have been made on the basis of surgical convenience, risk of complications, postoperative care, physiologic principles and personal belief. Surgeons who favor MT resection cite improved visualization and ease of surgical antrostomy, the removal of osteitic material, decreased synechiae formation postoperatively, and ease of post-operative management (Biedlingmaier, 1993;Biedlingmaier, Whelan, Zoarski, and Rothman, 1996;Havas and Lowinger, 2000;Rice, 1998;Shih, Chin, and Rice, 2003;Stewart, 1998;Stammberger, 1986). …”
Section: Introductionmentioning
confidence: 99%